Preservation of ovary function during combined treatment for cervical cancer - Yu. S. Sidorenko; G. A. Nerodo; O. E. Levchenko; P. A. Kruze (ABV-press, 2014)
Fixation of the preserved ovaries to uterine round ligament allow to retain ovarian function, not only during postoperative radiotherapy of stage Ib cervical cancer due to their transposition, but also after completing pelvic radiation because of preserved ovarian blood vessels in physiological place. This method prevents surgical and radiologic castration.